Effects of the competitor on antibody-hapten binding in immunoassays - Choi, J; Kim, C; Choi, MJ (TAYLOR & FRANCIS INC, 2002)
The effects of competitors on antibody (Ab)-hapten binding in an immunoassay were investigated using a goat anti-methamphetamine (MA) antibody (Ab). An N-4-aminobutyl derivative of methamphetamine (4-ABMA) was conjugated with keyhole limpet hemocyanine (KLH) and used as an immunogen. The antiserum was purified by affinity chromatography with various ligands, including 4-ABMA-protein conjugates, free haptens, and protein G. Direct and indirect competitive enzyme-linked immunosorbent assays (ELISA) were conducted with a competitor of 4-ABMA-fluorescein isothiocyanate (4-ABMA-FITC). The results were compared to those of ELISA with a different competing antigen, 4-ABMA-ovalbumin (4-ABMA-OVA), in terms of sensitivity and specificity. In both direct and indirect assay formats, the sensitivity was much improved with 4-ABMA-FITC, compared to that with 4-ABMA-OVA, suggesting that different labels on the same haptenic moiety for competitors considerably influence the assay performance. All the purified Abs also showed a distinct feature of strong affinity for benzphetamine with 4-ABMA-FITC, whereas they had their respective binding specificities with 4-ABMA-OVA. Comparing the results to those from other assay systems, we determined that the assay sensitivity was dependent on both the system and the competitor employed, and that the specificity was primarily dependent on the competitor used.
Keywords: REAGENT POLARIZATION FLUOROIMMUNOASSAY; CAPILLARY-ELECTROPHORESIS; PURIFICATION METHOD; METHAMPHETAMINE; SENSITIVITY; RADIOIMMUNOASSAY; OPTIMIZATION; SPECIFICITY; AFFINITY; TRACER